FACTORS AFFECTING PRE-HARVEST SPROUTING RESISTANCE IN WHEAT (TR ITICUM AESTIVUM L.): A REVIEW - X. Gao; C. H. Hu; H. Z. Li; Y. J. Yao; M. Meng; J. Dong; W. C. Zhao; Q. J. Chen; X. Y. Li (Journal of Animal and Plant Sciences, 2013)
Pre-harvest sprouting (PHS) is one of the most important factors to affect the yield and quality of crops worldwide especially in wet harvest period. Breeding PHS-resistant cultivars has important implications to improve the wheat quality and production. The PHS is determined by environmental conditions, inner factors and interaction between these factors. We here reviewed recent advances influencing factors of PHS, including seed dormancy, seed coat permeability and color, á-amylase activities, endogenous hormones levels, genes and QTLs. The present article will provide basic materials for mining new genes and developing new molecular makers to improve the tolerance of PHS in wheat as well as increase wheat production.
Keywords: wheat; pre-harvest sprouting (PHS); influencing factors; review; breeding